The response of bond prices to insurer ratings changes - Miao, Hong, author; Ramchander, Sanjay, author; Wang, Tianyang, author; The Geneva Papers on Risk and Insurance. Issues and Practice, publisher (Colorado State University. Libraries, 2014)
This paper examines the impact of insurer ratings changes on bond prices. Using insurer ratings from four major rating agencies and data covering the recent financial crisis period, we document that downgrades have a strong negative price impact on bond prices, especially when the downgrades are reinforced by multiple agencies. In contrast, the announcement-day impact of upgrades is found to be weak. Our evidence is consistent with the predictions of structural credit risk models.
Published as: The Geneva Papers on Risk and Insurance Issues and Practice, vol. 39, no. 2, September 2013, pp.389–413, https://doi.org/10.1057/gpp.2013.21.
Keywords: insurer ratings changes; ratings agency; bond price impact; event study